Binge watching bears: efficacy of real vs. virtual flagship exposure. Issue 2 (3rd April 2019) - Skibins, Jeffery C.; Sharp, Ryan L.
ABSTRACT: Advances in conservation psychology have demonstrated a growing public demand for connections to nature in general, and wildlife specifically. Charismatic megafauna have been used as flagship species, as they possess many characteristics to which the public can relate. Internet based webcams are emerging as an egalitarian mediator for bringing flagship exposure to the global public. This study examined if flagship exposure via a webcam was able to produce desired flagship responses, and if online responses were comparable to onsite experiences. A quantitative survey of Katmai National Park and Preserve brown bear viewers yielded 235 on-site and 5628 online responses. Real time, online viewing of brown bears was highly effective in generating flagship responses within viewers and the ability of online viewing to generate a positive emotional connection to bears was observed. Webcams can provide a global reach, minimize impacts, overcome socio-economic barriers, and provide multiple points of engagement across cultures.